Clinical and genetic profile of patients with primary hyperoxaluria: observation from a single centre from West India - Kapadia, Shahenaz; Vala, Kinnari; Saha, Anshuman; Banergy, Subho; Engineer, Divyesh; Patel, Himanshu; Kute, Vivek; Gera, Dinesh; Mishra, Vineet (International Journal of Contemporary Pediatrics, 2021)
Background: Primary hyperoxaluria (PH) is characterized by oxalate overproduction due to glyoxylate pathway enzyme defects in the liver. Apart from heterogeneous clinical manifestations of PH, diagnosis by urinary and plasma oxalate levels or stone analysis is not always confirmatory. Mutational analysis is required for definite diagnosis. There is heterogeneity between genotype of PH patients between Western and Indian population. The aim of this study is to describe clinical and genetic profile of Indian patients, diagnosed with PH in Western India. Methods: All clinical PH suspects in Nephrology and Paediatric Nephrology units from October 2016-September 2020, were counselled for genetic analysis for diagnostic confirmation. Cases, genetically confirmed to have PH, were included and retrospectively analysed for their clinical profile, modality of renal replacement therapy, survival/death. The mutations identified in our patients were compared with commonly prevalent mutations in world PH databases. Results: 13 of 15 patients were identified to have genetically confirmed PH. Median age at diagnosis was 1 year (range, 4 months to 46 years) and six (46.15%) were male. Six (46.15%) infants, two (15.38%) adolescents and five (38.46%) presented in adulthood. Nine presented as ESKD, while three patients progressed to ESKD during study. Eight (61.54%) with AGXT mutation were diagnosed as PH type1, four (30.76%) GRHPR mutation while one (7.69%) female infant had PH type 3 with HOGA mutation. Out of thirteen, five (38.46%) patients expired, five (38.46%) are ESKD requiring dialysis. Two (15.38%) post-transplant patients, graft loss for one and another requiring supportive medical management for deteriorating eGFR. Conclusions: ESKD being commonest presentation, high index of suspicion in all cases with renal stone and complete work up should be done for early diagnosis and timely intervention. National registry is required for detection of novel PH mutations in Indian population.